2017
DOI: 10.1186/s12711-016-0277-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence-based genomic prediction in laying chickens with different genomic relationship matrices to account for genetic architecture

Abstract: BackgroundWith the availability of next-generation sequencing technologies, genomic prediction based on whole-genome sequencing (WGS) data is now feasible in animal breeding schemes and was expected to lead to higher predictive ability, since such data may contain all genomic variants including causal mutations. Our objective was to compare prediction ability with high-density (HD) array data and WGS data in a commercial brown layer line with genomic best linear unbiased prediction (GBLUP) models using various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 55 publications
(73 reference statements)
5
57
0
Order By: Relevance
“…The bottom and top of the box represent first and third quartiles; the horizontal line denotes the median; the whiskers correspond to 1.5× interquartile distance; and dark dots are outliers. dissimilar results (Yang et al, 2011;Li et al, 2012;Koufariotis et al, 2014;Do et al, 2015;Abdollahi-Arpanahi et al, 2016;Ni et al, 2017). For instance, Ni et al (2017) reported slightly higher predictive ability using SNP within or around genes compared with whole-genome SNP data in laying chickens.…”
Section: Predictive Performance Of Alternative Snp Subsetsmentioning
confidence: 98%
See 1 more Smart Citation
“…The bottom and top of the box represent first and third quartiles; the horizontal line denotes the median; the whiskers correspond to 1.5× interquartile distance; and dark dots are outliers. dissimilar results (Yang et al, 2011;Li et al, 2012;Koufariotis et al, 2014;Do et al, 2015;Abdollahi-Arpanahi et al, 2016;Ni et al, 2017). For instance, Ni et al (2017) reported slightly higher predictive ability using SNP within or around genes compared with whole-genome SNP data in laying chickens.…”
Section: Predictive Performance Of Alternative Snp Subsetsmentioning
confidence: 98%
“…dissimilar results (Yang et al, 2011;Li et al, 2012;Koufariotis et al, 2014;Do et al, 2015;Abdollahi-Arpanahi et al, 2016;Ni et al, 2017). For instance, Ni et al (2017) reported slightly higher predictive ability using SNP within or around genes compared with whole-genome SNP data in laying chickens. Contrary, and Abdollahi-Arpanahi et al (2016) found that prediction based on genomic regions is trait dependent in broiler chickens, and in general the whole-genome approach provided better predictive ability than functional classes considered individually.…”
Section: Predictive Performance Of Alternative Snp Subsetsmentioning
confidence: 98%
“…Iheshiulor et al (2016) showed that the accuracy of genomic selection using sequencing data can be increased by up to 92% in a simulation study. However, when using real data, researchers can hardly achieve such attractive results (Heidaritabar et al, 2016;Ni et al, 2017;Elbasyoni et al, 2018). In plant breeding, Elbasyoni et al (2018) studied four traits in a winter wheat population and showed that high-throughput sequencing could achieve only comparable or even better accuracy than an SNP chip.…”
Section: Discussionmentioning
confidence: 99%
“…In plant breeding, Elbasyoni et al (2018) studied four traits in a winter wheat population and showed that high-throughput sequencing could achieve only comparable or even better accuracy than an SNP chip. In a commercial brown layer line, Ni et al (2017) compared genomic predictions for three egg-laying traits using genome-wide sequencing and a 336K SNP chip and reported that little or no benefit was gained when using all sequencing SNPs for genomic prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation